Diet and Mental Health During Emerging Adulthood: A Systematic Review. Issue 3 (June 2022) - Collins, Sam; Dash, Sarah; Allender, Steven; Jacka, Felice; Hoare, Erin
Previous research has reported associations between diet and risk of depression and anxiety; however, this is underexplored in emerging adulthood (EA; 18–29 years). This systematic review examined associations between diet quality and common mental disorders and their related symptomatology in the published EA literature. A systematic search according to Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines was conducted for articles published between 2009 and 2019. Grading of evidence was performed using an established quality assessment tool for quantitative studies. Sixteen studies were included for review. Findings supported EA as a risk period for both poor mental health and low diet quality. There was moderate support for associations between diet quality and depression, anxiety, positive/negative affect, suicide ideation, and psychological health. Methodological quality overall was weak. EA appears to be a critical period for both diet quality and mental health. Further research is needed to better understand diet and mental health associations among EAs.